Interação entre a Escola Básica e a Pós-graduação: uma rede de Pequenos Grupos de Pesquisa (PGP) - Carvalho, Lizete Maria Orquiza de [UNESP] (My University, 2015)
Given the objective of the Educational Observatory Program of putting in conjunction the efforts of graduation and basic school in order to improve the quality of the latter, are sought possibilities offered by such an arrangement for teacher education. The assumed action research methodology is designed as a collective rethinking about the social practice in which participants were immersed. It is identified strong correlation among the school/graduation interaction and the nature of the underlying teacher education design. The constitution of research questions accomplished inside the school and the centrality of Small Research Groups in a broad network of interactions were determinants.

Diante do objetivo do Programa Observatório da Educação de colocar em conjunção esforços da pós-graduação e da escola básica visando à melhoria da qualidade desta última, buscam-se possibilidades oferecidas por tal arranjo para a formação de professores. A metodologia de investigação-ação assumida é concebida como um repensar coletivo sobre a prática social em que os participantes estavam imersos. Identifica-se forte correspondência entre a interação escola/pós-graduação e a natureza da concepção de formação de professores subjacente. A constituição das questões de pesquisa realizada no interior da escola e a centralidade dos Pequenos Grupos de Pesquisa na rede ampla de interações mostraram-se determinantes.
Interaction between secondary and graduate school levels: a network of Small Research Groups (SRG)
Keywords: Teacher education; University-school interaction; Educational Observatory; Small research groups; Communicative action theory; Formação de professores; Interação Universidade-escola; Observatório da educação; Pequenos grupos de pesquisa; Teoria da ação comunicativa